A study to assess the prevalence of iodine deficiency disorders in Betul district, Madhya Pradesh, India - Kushwah, Sudarshan; Nair, Akhil R.; Meena, Jeevan Singh; Verma, Shipra; Sawlani, Harshima; Chandak, Ankit (International Journal Of Community Medicine And Public Health, 2019)
Background: Iodine deficiency disorders (IDD) constitute the single largest cause of preventable neurological damage worldwide. Majority of consequences of IDD are invisible and irreversible but at the same time these are preventable. The study was conducted to assess the prevalence of goiter in school children aged 6-12 years, to estimate the urinary iodine excretion and to assess the level of iodine concentration in salt samples obtained from households of selected school children. Methods: Population proportionate to size sampling. Sample size was 90 primary school-going children of age 6-12 years in each selected village, total 2700 from 30 villages/wards in Betul district, Madhya Pradesh, India. Results: The prevalence of goiter among the 6-12 years children was found to be 32.06%. Females had higher prevalence compared to males. Of the 540 salt samples, 370 (68.4%) had iodine concentration ≥15 ppm at household level. Conclusions: IDD is a mild public health problem in Betul district.